Patient motivators of postoperative electronic patient-reported outcome symptom monitoring use in thoracic surgery patients: a qualitative study - Meghan C. O'Leary; Elizabeth Kwong; Chase Cox; Amanda L. Gentry; Angela M. Stover; Maihan B. Vu; Jessica Carda-Auten; Jennifer Leeman; Gita N. Mody (SpringerOpen, 2024)
Abstract Background Electronic patient-reported outcome (ePRO) systems can be used to engage patients in remote symptom monitoring to support postoperative care. We interviewed thoracic surgery patients with ePRO experience to identify factors that influenced use of ePROs to report their symptoms post-discharge. Method This qualitative study used semi-structured telephone interviews with adults who underwent major thoracic surgery at an academic medical center in North Carolina. Individuals who enrolled in symptom monitoring, completed at least one ePRO survey, and were reachable by phone for the interview were included. The ePRO surveys assessed 10 symptoms, including validated Patient-Reported Outcome Common Terminology Criteria for Adverse Events (PRO-CTCAE) measures and thoracic surgery-specific questions. Surveys, offered via web-based and automated telephone options, were administered for four weeks post-discharge with alerts sent to clinicians for concerning symptoms. The interviews were guided by the Capability, Opportunity, Motivation model for behavior change (COM-B) and examined factors that influenced patients' completion of ePRO surveys post-discharge. Team members independently coded interviews and identified themes, informed by COM-B. We report descriptive statistics (demographics, number of surveys completed) and themes organized by COM-B components. Results Of 28 patients invited, 25 (89%) completed interviews from July to October 2022. Participants were a median 58 years, 56% female, 80% White, and 56% had a history of malignancy. They completed 131/150 (87%) possible ePRO surveys. For capability, participants reported building ePROs into their routine and having the skills and knowledge, but lacking physical and emotional energy, to complete ePROs. For opportunity, participants identified the ease and convenience of accessing ePROs and providers' validation of ePROs. Motivators were perceived benefits of a deepening connection to their clinical team, improved symptom management for themselves and others, and self-reflection about their recovery. Factors limiting motivation included lack of clarity about the purpose of ePROs and a disconnect between symptom items and individual recovery experience. Conclusions Patients described being motivated to complete ePROs when reinforced by clinicians and considered ePROs as valuable to their post-discharge experience. Future work should enhance ePRO patient education, improve provider alerts and communications about ePROs, and integrate options to capture patients' complex health journeys.